Survival in Patients With Metastatic Prostate Cancer Undergoing Radiotherapy: The Importance of Prostate-Specific Antigen-Based Stratification - Tian, Zijian; Meng, Lingfeng; Wang, Xin; Wang, Xuan; Ma, Tianming; Wang, Miao; Zhong, Qiuzi; Zhang, Yaqun; Liu, Ming (Frontiers in Oncology, 2021)
Objectives To explore the effectiveness of radiotherapy in mPCa patients with different PSA stratifications based on the cancer database of a large population. Background Screening criteria for patients with metastatic prostate cancer, who are candidates for radiotherapy, are rarely reported. Patients and Methods We identified 22,604 patients with metastatic prostate cancer in the Surveillance, Epidemiology, and End Results database and divided them into a radiotherapy group and a control group. Patients with metastatic prostate cancer were divided into subgroups according to their levels of prostate-specific antigen to evaluate the efficacy of radiotherapy. They were also divided into six subgroups according to their prostate-specific antigen levels. We used multivariate Cox analysis to evaluate overall survival and cancer-specific survival. After 1:1 propensity score matching, Kaplan-Meier analysis was used to explore the difference in overall survival and cancer-specific survival in the radiotherapy and control group. Results In all, 5,505 patients received radiotherapy, compared to 17,099 in the control group. In the multivariate Cox analysis, radiotherapy improved overall survival (hazard ratio [HR]: 0.730, 95% confidence interval [CI]: 0.636–0.838; P<0.001) and cancer-specific survival (HR: 0.764, 95% CI: 0.647–0.903; P=0.002) in patients with a PSA level of 4–10 ng/mL. Similar results were obtained by Kaplan-Meier analysis after 1:1 propensity score matching. In patients with prostate-specific antigen levels between 4–10 ng/mL, the overall survival (P<0.001) and cancer-specific survival (P<0.05) in the radiotherapy group was significantly better than those in the control group. Conclusion The result of this large population-based study shows that rigorous selection of appropriate metastatic prostate cancer patients for radiotherapy can benefit prognosis significantly. This can be the basis for future prospective trials.